(untitled) (Journal of Environmental Microbiology and Toxicology, 2024)
Lead pollution is a major global concern due to its harmful effects on the environment and human health, particularly within the aquaculture industry. This study examines the impact of lead exposure on Clarias gariepinus, a commercially significant catfish species used as a biomarker for environmental pollution. Lead exposure can disrupt enzyme activity, causing hematological, gastrointestinal, and neurological issues in both humans and animals. The research involved exposing C. gariepinus to varying concentrations of lead nitrate (Pb(NO3)2) and assessing behavioral, morphological, and physiological changes. This study revealed dose-dependent impairments in swimming, breathing, and feeding behaviors, highlighting the effect of lead exposure. Histological analysis of liver tissues showed cellular stress and damage, including vacuolization and mitochondrial irregularities. Additionally, the study measured cholinesterase (ChE) activity to assess the biochemical impact on liver function, noting a significant decrease of up to 40% in butyrylcholinesterase (BChE) activity with increased lead exposure. This supports the use of ChE activity as a potential biomarker for environmental pollution. Employing sentinel species like C. gariepinus in environmental risk assessments is crucial.